Infrared thermography for non-invasive measurement of social inequality aversion in rodents and potential usefulness for future animal-friendly studies - Watanabe, Shigeru (Frontiers in Behavioral Neuroscience, 2023)
Infrared thermography is a method that detects thermal radiation energy and can measure the body surface temperature of animals from a distance. While rectal temperature has traditionally been used to measure animals’ core temperature, thermal imaging can avoid the stress and potential rise of body temperature deriving from handling of the animals. Additionally, being non-invasive and contactless, thermal imaging allows free movement of the animals. The validity of this technique as a psychophysiological method has been proven in a series of stress-induced hyperthermia (SIH) studies of mice under social inequality conditions. Restraint in a holder elicits SIH in mice. A restrained mouse surrounded by freely moving cage mates displays increased SIH suggesting that social inequality enhances the stress. Social inequality can be examined also in unrestrained mice, in particular through unequal distribution of food. In this protocol, a food-deprived mouse is given a small piece of cheese, while its cage mate is given a large piece of cheese. This inequity causes SIH, suggesting social inequality aversion in mice. Thus, social inequality in different situations similarly increased SIH. Importantly, in future studies infrared thermography could also be used to evaluate emotional arousal states different from stress (for example to assess reactivity to rewards or in social and sexual preference tests). Moreover, the technique could be used to investigate also cognitive arousal induced by novelty. Indeed, infrared thermography could be a particularly useful tool for animal-friendly studies of cognition and emotion in rodents.